Penyalahgunaan Narkotika Oleh Remaja di Kota Jambi dalam Perspektif Kriminologi - Zamzimi, Padlan; Yanti, Herma (Wajah Hukum, 2026)
This study aims to determine the factors that cause drug abuse by adolescents in Jambi City and to determine law enforcement in narcotics abuse by adolescents in Jambi City. this type of research is empirical juridical. The result of the research is that the factors that cause adolescents to abuse narcotics in Jambi City cannot be separated from parental control, because parents should protect, educate and provide a decent life both in terms of physical and psychological needs. Parents are expected to supervise and educate their children to always stay away from drug abuse. By providing religious education and general education. The young generation is the backbone of the nation and state. Law enforcement is carried out in overcoming narcotics abuse by teenagers, namely by conducting investigations, investigations and rehabilitation. In practice, law enforcement carried out in Jambi City with all the obstacles experienced, is sufficient in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. However, the Jambi City Police in handling cases of drug abuse committed by children have never been done by diversion. In addition to settlements that are not diverted, juveniles who are in the judicial process are not detained, either at the stage of investigation, investigation, and prosecution. The child awaits the court's decision by making a mandatory report, with parental guarantees that the child's presence, the obligation to report, do not run away, and do not damage the evidence.